Farmer Satisfaction with Financing Services at Sharia Microfinance Institutions Agribusiness (Sharia MFI-A) - Widya Fitriana (Islamic Economics Journal, 2024)
The total share of financing for the agricultural sector from financial institutions in Indonesia is still relatively low. It is because the agriculture sector is considered high-risk and not bankable. Even though the demand for financing from the agricultural sector is very high. Sharia MFI-A is a financing institution friendly to farmers because it has Sharia principles and shares risks. The loyalty of its customers determines the sustainability of this business. Service quality and customer expectation are affect customer satisfaction. This study aims to analyze service attributes considered necessary by customers and customer satisfaction to financing services at Sharia MFI-A. This research was conducted in West Sumatra, a province famous for its local principles of “Adat basandi sayarak, syarak basandi kitabullah”. The research was conducted on Sharia MFI-A namely in Agam Regency. The respondents were farmers who received financing in 2022. Five variables were observed: tangible, reliability, responsiveness, assurance, and empathy and measured using the Likert scale. Data analysis used Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI). The results showed that CSI’s score on Sharia MFI-A services is 88.28%, including the range of very satisfied criteria. Customers expressed very satisfaction with the performance of Sharia MFI-A services because the office is clean and comfortable, fast and friendly service, guaranteed customer confidentiality, and proft sharing transparency. T his is by the principles of sharia services, namely fairness, and honesty in transactions (‘adl wa tawazun), maslahah, and does not contain gharar and riba. Customer satisfaction with the services will affect farmers’ loyalty to utilizing financing services from Sharia MFI-A in the future.